2021
DOI: 10.3389/fpsyt.2021.606147
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Integration and Radicalization Prevention Programs for Migrants in the US, Canada, and Europe

Abstract: Background: International migration processes are some of the most important events of our time. Migrating implies a broad range of factors that affect integration, and which may be linked to radicalization. Host countries use different methods for the integration of migrants. The aim of this systematic review is to analyze intervention programs that aim at promoting social integration and preventing the radicalization of migrants, with the objective of studying actions carried out in the US, Canada, and Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…Other studies have shown that participating in social activities created opportunities for social engagement and led to the formation of new social ties, acting as important sources of social support for individuals (CCSDH, 2015; Kauffman, 2021; Mamatis et al , 2019). Although this study did not assess the ID card’s impact on health, it has been widely reported that through increased social ties and social support comes a reduction in social isolation and depression and better mental health outcomes (Del Pino-Brunet et al , 2021; Fakhoury et al , 2021; Mamatis et al , 2019; UNDESA, 2016). Thus, increased participation in society may not only lower the risk for social exclusion by fostering social ties but has the potential to promote health and well-being for MPS living in communities with ID card programs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have shown that participating in social activities created opportunities for social engagement and led to the formation of new social ties, acting as important sources of social support for individuals (CCSDH, 2015; Kauffman, 2021; Mamatis et al , 2019). Although this study did not assess the ID card’s impact on health, it has been widely reported that through increased social ties and social support comes a reduction in social isolation and depression and better mental health outcomes (Del Pino-Brunet et al , 2021; Fakhoury et al , 2021; Mamatis et al , 2019; UNDESA, 2016). Thus, increased participation in society may not only lower the risk for social exclusion by fostering social ties but has the potential to promote health and well-being for MPS living in communities with ID card programs.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, findings showed that participants who used the ID card were more likely to perceive increased control/independence in their lives and have more opportunities for civic engagement, indicators of enhanced empowerment (Trezona, 2019). A systematic review by Del Pino-Brunet et al (2021) found that through civic engagement, migrants tend to experience higher levels of self-confidence and self-esteem, which can enhance perception of agency over one’s life circumstances. Other studies have further linked civic engagement with better physical and psychological health benefits, including greater life satisfaction (Jenkinson et al , 2013; Swaner, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effectiveness has been assessed for various categories of outcomes since this strategy can impact many levels. More specifically, the findings have shown significant reductions in the symptoms of depression, anxiety, PTSD, hyperactivity and functional impairment [9,31,32,35]. Positive results have also been shown for general well-being, emotional adjustment, and relational problems [9].…”
Section: Creative and Expressive Techniquesmentioning
confidence: 91%